STUDI KASUS: PAKET EDUKASI “BREAST” UNTUK PENANGANAN MASALAH LAKTASI - Viqy Lestaluhu (Poltekkes Kemenkes Maluku, 2022)
Breastfeeding is a government program that must be carried out by mothers after giving birth until the baby aged six months old and even up to two years, because breastfeeding has many benefits, especially for the mother and baby. However, it is undeniable that the fact among the community shows that breastfeeding is actually not easy, many mothers fail in the breastfeeding process and this can affect the health of the mother and baby. The largest average decrease in maintaining breastfeeding occurred in the first week postpartum. Knowledge and correct understanding of breast milk also plays an important role in this regard. Both knowledge about the advantages and benefits of breastfeeding, how to overcome the obstacles faced during breastfeeding, as well as the correct breastfeeding technique. This case study describes the application of the “BREAST” education package to Mrs. A. 6 hours postpartum with complaints of lack of milk production. One of the midwifery care for breastfeeding mothers is to implement the